2020
DOI: 10.1016/j.ejmech.2020.112864
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of organoselenium (NSAIDs-SeCN and SeCF3) derivatives as potential anticancer agents

Abstract: A series of organoselenium compounds based on the hybridization of nonsteroidal antiinflammatory drugs (NSAIDs) scaffolds and Se functionalities (-SeCN and -SeCF 3 ) were synthesized and characterized, and evaluated against four types of cancer cell lines, SW480 (human colon adenocarcinoma cells), HeLa (human cervical cancer cells), A549 (human lung carcinoma cells), MCF-7 (human breast adenocarcinoma cells). Interestingly, most of the investigated compounds showed active in reducing the viability of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…Some CF 3 Se-containing compounds have already exhibited properties that are amenable to potential anticancer drug development. [8] With more efforts devoted to exploring the altered properties of the trifluoromethylselenylated compounds, CF 3 Se-containing drugs will likely be developed in the near future. Last but not least, methodologies for the enantioselective synthesis of trifluoromethyselenolated compounds are underexplored and need to be developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CF 3 Se-containing compounds have already exhibited properties that are amenable to potential anticancer drug development. [8] With more efforts devoted to exploring the altered properties of the trifluoromethylselenylated compounds, CF 3 Se-containing drugs will likely be developed in the near future. Last but not least, methodologies for the enantioselective synthesis of trifluoromethyselenolated compounds are underexplored and need to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang and coworkers have developed the trifluoromethylselenolated nonsteroidal anti-inflammatory drugs (NSAIDs) that showed promising results on cancer cell viability, antioxidant activity and in docking studies, providing promising new lead compounds for future anti-cancer drug development. [8] Therefore, more and more research groups have shown a great interest in trifluoromethylselenolation chemistry. For the synthesis of trifluoromethylselenolated compounds, there have been two main approaches: indirect and direct introduction.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in synthetic organoselenium compounds, mainly due to their properties as synthetic intermediates in organic transformations [ 1 , 2 , 3 ] and material sciences [ 4 , 5 ], as well as in medicinal chemistry [ 6 , 7 , 8 , 9 ]. These compounds have been recently described as good antioxidants [ 10 , 11 ], also presenting anti-inflammatory [ 12 , 13 ], antibacterial [ 14 ], antiviral [ 15 ], anticancer [ 16 , 17 , 18 , 19 ], anti-Alzheimer’s [ 20 , 21 , 22 , 23 ] and other activities [ 24 , 25 , 26 , 27 , 28 ]. Furthermore, in relation to the current pandemic of COVID-19, there are some interesting studies available that demonstrate the effectiveness of organoselenium compound (Ebselen) as an antiviral molecule, Figure 1 [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence in the literature has illustrated that among the different selenated scaffolds, selenenocyanate [19,20] and diselenide [21][22][23] fragments are important pharmacophores that significantly suppress breast cancer. Furthermore, our research group has reported that selenocyanate and diselenide entities possess potent antitumor activity [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%